Distributed real‐time rendering for ultrahigh‐resolution multiscreen 3D display. Issue 3 (6th January 2022) - Chen, Yingying; Sang, Xinzhu; Li, Yuanhang; Xing, Shujun; Guan, Yanxin; Yan, Binbin; Wang, Kuiru
Abstract: Large‐scale autostereoscopic three‐dimensional (3D) displays can give audiences a truly immersive feeling with strong visual impact. However, the traditional autostereoscopic 3D display systems are limited by the display hardware, making it difficult to directly achieve large‐scale 3D displays with high resolution. Multiscreen splicing with laser backlights can be used for large‐scale and ultrahigh‐resolution 3D display, but it normally results in subscreen image asynchronization, view zone error, or obvious edge overlapping. To solve the problems mentioned above, a distributed real‐time rendering system for ultrahigh‐resolution multiscreen 3D display is proposed. Fifteen 3D LCD display devices are driven through a host, cooperating with laser backlights, a lenticular lens array (LLA), and a directional diffuser to display high resolution, high frame rate, large size, and wide‐viewing angle 3D images. The resolution of the whole display system can reach 23, 040 × 21, 600. The rendering system provides a large‐scale and real‐time 3D scene image with an ultrahigh‐definition resolution at a speed of 40 frames per second and high quality. Abstract : We designed a distributed real‐time rendering system for ultrahigh‐resolution multiscreen 3D display. The rendering system provides a large‐scale and real‐time 3D scene image with an ultrahigh‐definition resolution at a speed of 40 frames per second with high quality. The system can realize real‐time high‐definition natural‐transition true 3D image cooperated with large‐scale autostereoscopic displays hardware system.